Experimental study of vertical slat screens effects on reducing shallow water sloshing in a tank under horizontal excitation with a wide frequency range. (1st February 2019) - Yu, Liting; Xue, Mi-An; Zheng, Jinhai
Abstract: The screen-affected sloshing with a wide excitation frequency including the third and the fifth mode frequencies were investigated experimentally by varying solidity ratio, slot size, location and slat screen number. The maximum surface elevation decreases as solidity ratio increases when frequencies are not changed obviously due to screens inside tanks. Effects of slat screen on sloshing are related to solidity ratio and frequency. One vertical screen fails in significantly suppressing sloshing excited by the third mode horizontal excitation. Two slat screens can effectively reduce sloshing excited by horizontal excitation with a relatively wide frequency range and the recommended screen positions are presented according to excitation frequencies. Sloshing reduction does not always apparently increase as screen number increases under the screen positions specified in experiments. Sloshing amplitude with two slat screens may be greater than that with one slat screen located at tank centre when frequency is near the fifth-mode or third-mode frequency depending on two screens positions. Though wave amplitudes reductions are a little more noticeable in tank with 5 mm slot size screen than those in tank with 50 mm slot size screen, wave frequency components with 5 mm slot size screen are much simpler than those with 50 mm slot size screen.